Evaluation of antibiotic combination of Litsea cubeba essential oil on Vibrio parahaemolyticus inhibition mechanism and anti-biofilm ability. (July 2022) - Li, Anqi; Shi, Chenglong; Qian, Senhe; Wang, Zhou; Zhao, Shiguang; Liu, Yan; Xue, Zhenglian
Abstract: Vibrio parahaemolyticus ( V. parahaemolyticus ) is a common pathogen in seafood. The use of antibiotics is a primary tool to prevent and control V. parahaemolyticus in the aquaculture industry. However, V. parahaemolyticus combats the damage caused by antibiotics by forming biofilms under certain conditions. In this study, we analyzed the antibacterial effect and the characteristics of V. parahaemolyticus by experimentally determining the minimum inhibitory concentration (MIC) and the fractional inhibitory concentration index (FICI) values of a combination of the Litsea cubeba essential oil (LCEO) and several commonly used V. parahaemolyticus antibiotics. The bactericidal effect of the essential oil alone and essential oil in combination with the antibiotics were evaluated with time-kill curves. The damage to cell membranes and cell walls were assessed by measuring the content of macromolecules and alkaline phosphatase (AKP) released into the supernatant using V. parahaemolyticus ATCC17802 as the experimental strain. The membrane structure was observed by transmission electron microscopy. The results showed that the MIC value of the LCEO was 1, 024 μg/mL, and the LCEO FICI values in combination with tetracycline or oxytetracycline hydrochloride was 0.3125 and 0.75, respectively, indicating synergistic and additive effects. Moreover, LCEO inhibited the growth and promoted the removal of biofilms by reducing the content of hydrophobic and extracellular polysaccharides on the cell surface. This study provides a reference for studying the antibacterial activity of LCEO and the combination of antibiotics to prevent and control the formation of biofilms by V. parahaemolyticus . Highlights: LCEO showed significant antibacterial activity against V. parahaemolyticus . LCEO exerted its antibacterial activity mainly by an action mode of membrane damage. LCEO had synergistic effect in combination with tetracycline. LCEO decreased the amount of antibiotics needed to inhibit and remove the biofilm. LCEO down-regulated the gene tolC and ompW involving the drug resistance.